Emerging mini electric cars in China: User experience and policy implications. (April 2019) - Ling, Ziwen; Cherry, Christopher R.; Yang, Hongtai
Highlights: Mini-EVs are emerging in China with potential benefits but little regulation. We interview Mini-EV owners in China, who are older, high income, and unlicensed. Users transitioned from e-bikes and public transit due to perceived safety and cost. Mini-EVs provide mobility benefits but don't likely lower energy use or emissions. Drivers should have graduated licenses and be relegated to low-speed roads. Abstract: Mini electric cars (mini-EVs) are gaining popularity in many areas in China (∼4–5 million ownership). Mini-EVs are a class of enclosed vehicle smaller than conventional cars. The average range of a mini-EVs is about 100 km, with a maximum speed ranging from 40 to 60 km/h. Their adoption has generated regulatory uncertainty and their classification is ambiguous. While there have been many studies focused on New Energy Vehicles (NEV) (e.g., battery electric conventional car) acceptance rates, purchase intention, and driving behavior; little research has focused on mini-EVs. This paper relies on structured interviews to shed initial light the motives for mini-EV choice and purchase, model choice, travel behavior, and safety. The intention of this paper is to explore key market issues for further analysis and policy intervention; specifically, we aim to profile users and use patterns to inform policy on vehicle standards, licensing, on-road regulations, and subsidy policy. This is the first paper to do this. In-depth interviews with 34 mini-EV owners in Kunming, China reveal an owner profile that is predominately retired male with high household income. Less than half of users have a driver license. Their purchase motives are mostly driven by their age or physical limitations, the convenience and low cost of the vehicle and charging, and the vehicles' low speed. Most users transitioned from using e-bikes and public transit. Policy implications include standardizing mini-EVs designs, imposing a license system for mini-EVs and their users, and sustaining low-speed vehicle infrastructure.